2020
DOI: 10.1161/strokeaha.120.030427
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Targeting Racial/Ethnic Disparities in Stroke Prevention and Treatment

Abstract: Systemic racism is a public health crisis. Systemic racism and racial/ethnic injustice produce racial/ethnic disparities in health care and health. Substantial racial/ethnic disparities in stroke care and health exist and result predominantly from unequal treatment. This special report aims to summarize selected interventions to reduce racial/ethnic disparities in stroke prevention and treatment. It reviews the social determinants of health and the determinants of racial/ethnic disparities in care. It provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 60 publications
3
102
1
1
Order By: Relevance
“…Moreover, there was no statistically significant interaction between DTN and sociodemographic characteristics on the 30-day, 1-year, or 2-year mortality, indicating that all socio-demographic groups benefited equally from faster DTN times. The findings of our study further reinforce the need to implement specific interventions to reduce racial/ethnic disparities, improve stroke awareness and access to stroke healthcare among racial minorities ( 27 ).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, there was no statistically significant interaction between DTN and sociodemographic characteristics on the 30-day, 1-year, or 2-year mortality, indicating that all socio-demographic groups benefited equally from faster DTN times. The findings of our study further reinforce the need to implement specific interventions to reduce racial/ethnic disparities, improve stroke awareness and access to stroke healthcare among racial minorities ( 27 ).…”
Section: Discussionsupporting
confidence: 72%
“…It should be noted that the observed stroke disparities by race/ethnicity are likely to be attributed to racial-ethnic minority groups such as non-Hispanic Blacks' limited access to quality care and lower socioeconomic status, which resulted in their higher prevalence and worse control of traditional vascular risk factors. [43][44][45] Using stroke cases from hospitalization data, this study took a step forward in identifying the association between 9/11-related PTSD, dust exposure, and stroke subtype as compared with our first study, which used self-reported stroke. However, the results should still be interpreted with caution as there are several limitations to note.…”
Section: Resultsmentioning
confidence: 99%
“…When we compared the significance and magnitude of PTSD impact on stroke, it was clear that PTSD played an even larger role than sex (male) and race (non‐Hispanic Black) in this population. It should be noted that the observed stroke disparities by race/ethnicity are likely to be attributed to racial‐ethnic minority groups such as non‐Hispanic Blacks' limited access to quality care and lower socioeconomic status, which resulted in their higher prevalence and worse control of traditional vascular risk factors 43–45 …”
Section: Discussionmentioning
confidence: 99%
“…When assessing health care disparities, it is important to consider patient-, neighborhood-, and health system-level factors affecting the access, availability, and utilization of health care resources. Patients with demographic characteristics subject to traditional disparities-Black race, female sex, older age, Medicaid insurance type, and lower income level-have historically experienced greater stroke morbidity and mortality than their more advantaged counterparts [2,3,[11][12][13][14][15][16][17][18][19][20][21]. Although imaging and treatment of patients with stroke are performed according to guidelines, care variability and implicit biases exist, and prior research has demonstrated that imaging and treatment are not utilized equally across different populations.…”
Section: Introductionmentioning
confidence: 99%